Acupuncture Prevent Progression of Cachexia in Breast Cancer in Outpatients of Dr. Saiful Anwar General Hospital Malang East Java Indonesia - Laily yuliatun (Journal of Global Pharma Technology, 2019)
Objective: This study was aimed to assess effect of acupuncture in progression of cachexia in breast cancer patient. Indicator progression of cachexia in this study is level of BMI, FM and FFM was measured before and after eight session of acupuncture procedure.Methods: Seven patients were diagnosed breast cancer provide eight acupuncture session before chemotherapy and radiotherapy procedure. Acupuncture procedure was done every 2 days, with duration 30 minutes for every session. Bioelectrical impedance analysis (BIA) measurements were taken at before and after eight acupuncture session to evaluate the body composition of patients. BIA is fast, inexpensive and noninvasive method for evaluating Body Mass Index (BMI), Fat Mass (FM) and Fat-Free Mass (FFM).Results and Conclusion: All patients were include in the analysis were complete the acupuncture intervention and BIA measurements. Average age was 54 years, with rang 47-58 years. Most of patients in advanced cancer, 28.5% stage 3 and 43% in stage 4. In this study acupuncture could prevent progression of breast cancer cachexia, with maintain body composition during procedure. BMI was relative constant after eight session of acupuncture (20.25±3.1; p>0.00). Similarly, from BIA measurement, FFM decrease only 0.4% (p>0.05) and FM increase 0.4% (p>0.05). The constant value of body composition mean acupuncture could maintain the metabolism rate in cachexia patients. This study indicate acupuncture could prevent progression of cachexia in breast cancer. Keywords: Acupuncture, Cachexia, Breast Cancer, Body composition.